Ethno-Medicinal Plants used for the Treatment of Various Skin Disorders by the Garo Community in West Garo Hills District of Meghalaya - Marak, Naldarine M.; Lalnundanga (Indian Forester, 2018)
The ethno-medicinal study based on the treatment of various skin disorders was conducted in six developmental blocks of West Garo Hills district of Meghalaya predominantly inhabited by Garo community during the year 2014-2016.Application of a traditional Garo herbal medicine in the treatment of skin disorders is widespread. The tribal knowledge plays a very crucial role in ethno-medicinal research because they are the source of information and knowledge which inherited from their ancestors from generations to generations. Skin diseases are the most common form of infections occurring in people of all ages. The symptoms of skin infection can vary depending on its type. In this research a total of 20 plants species used for the treatment of various skin disorders have been documented which includes botanical name of the plant, prevalent local name, uses, formulations and also mode of administration.